2014
DOI: 10.1155/2014/282980
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Time to Return to Training for Stress Fractures during Military Basic Training

Abstract: Currently, little is known about the length of time required to rehabilitate patients from stress fractures and their return to preinjury level of physical activity. Previous studies have looked at the return to sport in athletes, in a general population, where rehabilitation is not as controlled as within a captive military population. In this study, a longitudinal prospective epidemiological database was assessed to determine the incidence of stress fractures and the time taken to rehabilitate recruits to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 17 publications
(30 reference statements)
5
32
0
1
Order By: Relevance
“…The distribution of sites of SF in this study is similar to the study by Singh SC, et al, [9]. However, in contrast Alexander M Wood et al, reported metatarsals as the most common site for stress fracture [3].…”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…The distribution of sites of SF in this study is similar to the study by Singh SC, et al, [9]. However, in contrast Alexander M Wood et al, reported metatarsals as the most common site for stress fracture [3].…”
Section: Methodssupporting
confidence: 88%
“…It is thus likely that the incidence, we reported, could have been even higher if a bone scan or an additional scintigraphy was performed. Return to full activity has been reported at 12.2 weeks for metatarsal fractures to 21.1 weeks for tibial stress fractures [3]. In our case, all cadets returned to their full activity in an average period of nine weeks.…”
Section: Methodssupporting
confidence: 53%
See 1 more Smart Citation
“…Recognised amongst MSKI as the cause for the greatest amount of time lost out of training and therefore representing significant impact on organisational effectiveness, stress fractures, a sub-classification of overuse MSKI, have received considerable attention across the literature. Presenting in the pelvis, spine and less frequently in the upper limb, as much as 90% of all stress fractures are lower limb with incidence rates reported to range from 0.7 to 20% across both civilian and military populations [8,9,19,41,42]. Prospective data in recruits undergoing basic training indicates stress fracture incidence of 3.3% to 8.5% in the US military, 15% among Indian Army recruits and as much as 31% in Israeli Army recruits [41,43].…”
Section: Injury Typementioning
confidence: 99%
“…Prospective data in recruits undergoing basic training indicates stress fracture incidence of 3.3% to 8.5% in the US military, 15% among Indian Army recruits and as much as 31% in Israeli Army recruits [41,43]. Incidence of 5% reported in the Royal Marines [42] compares favourably to the 6% incidence reported in United States Marine Corps (USMC) recruits [44] and to the 5-9% reported among US SEAL Trainees [45]. The insidious onset of these prevalent injuries has been attributed to sustained repetitive strenuous activity which in turn indicates the requirement to investigate the nature of training within individual environments [6].…”
Section: Injury Typementioning
confidence: 99%